Disputes, debt and equity - Alfred Duncan; Charles Nolan (University of Kent, School of Economics, 2017)
We show how the prospect of disputes over firms' revenue reports promotes debt financing over equity. These findings are presented within a costly state verification model with a risk averse entrepreneur. The prospect of disputes encourages incentive contracts that limit penalties and avoid stochastic monitoring, even when the lender can commit to stochastic monitoring strategies. Consequently, optimal contracts shift away from equity and toward standard debt. For a useful special case of the model, closed form solutions are presented for leverage and consumption allocations under efficient debt contracts. Some empirical implications of the theory are pursued.
Keywords: D52; D53; D82; D86; 330; Microeconomics; costly state verification; external finance; leverage